Developing a Methodology to Support the Bidding Decision for Contractors in Syria - جراد فايز; الحايك انس (Latakia University Journal -Engineering Sciences Series, 2021)
The construction sector is considered one of the most important sectors in various countries of the world due to the large sums invested in this sector compared to other sectors. This research confirms the importance of competition in this sector. In addition, the benefit of this competition for the public sector to choose the best offers and urge contractors to compete to provide the best services at the lowest prices. Most contractors rely on experience in previous projects when deciding to enter the bid. This leads to haste as a result of not studying all the factors affecting the decision, as well as the difference in the method of determining the percentage of addition or deduction from one contractor to another, which leads to a discrepancy in the financial offers between contractors. This research provides a methodology to assist the contractor in supporting his decision to enter the bid or not by studying all the factors affecting this decision, the research also proposes a methodology that helps the contractor to determine the percentage of addition or deduction according to the way of thinking of each contractor Compatible with the nature of the project’s terms. This was done through the development of three basic methods (the importance indicator method for the item - the fixed profit percentage method - the financial mass method for the item). The proposed model provides a comparison between the three methods while providing a guide that directs the contractor to the most appropriate method according to the nature of the project.